Experimental investigation of the influence of column scale, gas density and liquid properties on gas holdup in bubble columns. (October 2015) - Rollbusch, Philipp; Becker, Marc; Ludwig, Martina; Bieberle, Andrè; Grünewald, Marcus; Hampel, Uwe; Franke, Robert
Highlights: Highlights the need for experimental data at processing conditions. Utilized organic solvents at large scale and pressurized conditions. Investigated influence of scale on gas holdup. Examined axial holdup profiles. Abstract: Measurements of gas holdups in bubble columns of 0.16, 0.30 and 0.33 m diameter were carried out. These columns were operated in co-current flow of gas and liquid phases and in semibatch mode. The column of 0.33 m diameter was operated at elevated pressures of up to 3.6 MPa. Nitrogen was employed as the gas phase and deionized water, aqueous solutions of ethanol and acetone and pure acetone and cumene as the liquid phase. The effects of differing liquid properties, gas density (due to elevated pressure), temperature, column diameter and superficial liquid velocity on gas holdup were studied. The gas holdup measurements were utilized by differential pressure measurements at different positions along the height of the bubble columns which allowed for the identification of axial gas holdup profiles. A decrease of gas holdup with increasing column diameter and an increase of gas holdup with increasing pressure was observed. The effect of a slightly decreasing gas holdup with increasing liquid velocity was found to exist at smaller column diameters. The use of organic solvents as the liquid phase resulted in a significant increase in gas holdup compared to deionized water. It is found that published gas holdup models are mostly unable to predict the results obtained in this study.